Zasady zarządzania serwisami społecznościowymi w bibliotekach .......... 35 - Wachowicz, Monika; Antczak, Mariola (Skąd się biorą czytelnicy?, 2025)
THE RULES OF SOCIAL NETWORKING SERVICES MANAGEMENT IN LIBRARIESIn the age of the digital transformation, it is becoming more and more common for libraries to use internet social platforms as tools of communication with their users and of promoting their resources and services. The aim of the study was to gather and systematize the rules of social networking services management, which has not been discussed comprehensively in the literature so far. The authors made a review of the relevant literature as well as incorporatingtheir own observations and insights that helped to formulate their original set of rules. The rules fall into five major categories: strategy, promotion of library profiles, considering the needs of clients, building their commitment, and the management of the public image of the library. On top of that, four directives for the library management staff were created. The research was based on the bibliographical method, review and critique of the literature, the heuristic method, and an analysis of the content of the library profiles in social media.